Examining the impediments to conflict management in West Africa: a study of the ECOWAS interventions in Liberia (1990) and Cote d'Ivoire (2010) - Ampomah, Emmanuel (Department of Political Studies, 2020)
Although established to promote economic integration in West Africa, ECOWAS has transformed into a regional security organization concerned with terminating conflicts in the sub-region. Accordingly, ECOWAS has militarily intervened in the numerous conflicts in the sub-region including the Liberian and Ivorian civil wars. The study notes that the fundamental causes of conflicts in the sub-region have not changed, although their dynamics have changed in many ways. Similarly, the approach of member states towards conflict resolution has changed remarkably with time, evidenced by the easing of the Anglo-Francophone tensions within the community. However, ECOWAS faces challenges in its conflict management role, including financial and logistical constraints, lack of consensus on the deployment of ECOMOG, lack of neutrality in peacekeeping operations, and its heavy reliance on Nigeria’s leadership in interventions. These and other impediments have vitiated ECOWAS’s capacity to swiftly intervene in conflict situations. The study concludes that, overcoming the challenges confronting it increases the capacity of ECOWAS to manage conflicts in the region.